Possibilities of Distance Learning Tools in Teaching and Learning Technical Subjects - Osadchyi, Viacheslav; Osadcha, Kateryna (Pedagogical Discourse, 2017)
The specifics of teaching technical subjects demands certain tools for development of students technical skills in modeling, programming, engineering, construction and design from distance technologies. The paper analyzes the possibilities of modern information technology in organization of distance learning of technical subjects, namely the platform of distance learning (Moodle and edX), including massive open online course (MVOK) program to create SCORM-packages and 3D- objects for visualization and simulation. The analysis of plug-ins (Virtual programming lab module «Activities», EJSApp), which help manage the programming tasks such as writing and changing the source code; setting the interactive mode of the program, launching a compiler; searching for similarities between files; setting limits in editing and external pasting is carried out. Some platforms for learning software engineering disciplines are analyzed. Functional possibilities of developed software simulators that implement practice-oriented methods of acquiring necessary professional skills are defined. The use of such simulators makes it possible to provide students with the opportunity to develop their ability to work with technical disciplines without equipment and data damage on training computers. The most common applications for the creation of electronic courses (Microsoft LCDS, Adobe Captivate), interactive learning materials (CourseLab) are presented. According to the conducted analysis of the software for distance learning and their own experience in the creation and management of online courses the authors determined the platform that had enough possibilities for teaching technical subjects. Key words: distance learning technologies, massive open online course, SCORM, 3D-objects, virtualization, simulation